Varietal Preference of Mango fruit Borer Autocharis albizonalis Hampson in Regard to the Phenol Content of the Fruit - Bhattacharyya, Mainak (International Journal of Bio-resource and Stress Management, 2018)
Varietal preference of mango fruit borer (Autocharis albizonalis Hampson ) was determined in regard to the Phenol content of the fruit in Department of Plant Physiology, Bidhan Chandra Krishi Viswavidyalaya, Mohanpur, Nadia, West Bengal. Total estimation of Phenol was carried out with the Folin-Ciocalteau reagent. It was determined that pulp phenol level of the fruits of the mango cultivars ranged from 5.707 mg kg-1 to 23.57 mg kg-1 at marble stage, 2.537 mg kg-1 to 13.493 mg kg-1 at egg stage and from 1.023 mg kg-1 to 11.023 mg kg-1 at maturity stage of the fruit. The variations in pulp phenol level of mango cultivars under study were significant at all three stages indicating inherent differences in this respect among the cultivars. Himasagar at marble stage had phenol content 21.060 mg kg-1 in the pulp. Gradually, the phenol content declined to 11.023 mg kg-1 in the pulp at maturity when infestation of the pest on the variety reached its highest. The correlation study of fruit borer infestation revealed that its infestation was strongly associated with pulp phenol level of fruit maturity (r=0.78) and egg stage (r=0.73) where as it did not have any association with pulp phenol level at marble stage (r=0.44).